Adherence to the EAT-Lancet Diet is Not Associated With Weight Status in a Latin American Urban Multicentric Study - Rulamán Vargas-Quesada; Rafael Monge-Rojas; Juan José Romero-Zúñiga; Carolina Araya-Bastias; Irina Kovalskys; Marianella Herrera-Cuenca; Lilia Yadira Cortés; Martha Cecilia Yépez García; Reyna Liria-Domínguez; Attilio Rigotti; Mauro Fisberg; Georgina Gómez (Advances in Public Health)
The overweight/obesity high prevalence and the effects of climate change in Latin America underscores the possible positive outcomes of adopting a healthy and sustainable diet to respond to the region’s burden of nutrition-related noncommunicable diseases (NCDs). However, research on adherence to the EAT-Lancet diet in Latin America and its association with overweight/obesity is limited. This study explores the relationship between the EAT-Lancet diet adherence and overweight/obesity in a cross-sectional and urban multicentric study involving 6683 participants aged 15–65. Adherence to the EAT-Lancet diet was evaluated using the Planetary Health Diet Index (PHDI). The findings indicate that high adherence to the EAT-Lancet diet (fifth quintile) was not significantly associated with overweight/obesity (reference: first PHDI quintile, PR: 1.057, CI: 0.993–1.125, p-trend = 0.140) after adjusting for key covariates. Equivalent outcomes were found when assessing adherence to the EAT-Lancet diet using the EAT-Lancet Index, the World Index for Sustainability and Health (WISH), and the Healthy and Sustainable Diet Index (HSDI), after adjusting for the same variables. The persistently high prevalence of overweight/obesity among different adherence levels to the dietary pattern and the study’s design, do not appear to be the key factors contributing to the lack of association between these variables. Instead, the considerably low adherence to the EAT-Lancet diet in the sample as well as the low variability in adherence across participants with and without excess weight might help explain the lack of observed association. However, further research is needed to verify this conclusion.